Pengaruh Teknik Relaksasi Benson Terhadap Tingkat Depresi Lansia Di Panti Sosial Lanjut Usia Harapan Kita Palembang Tahun 2022: Pengaruh Teknik Relaksasi Benson Terhadap Tingkat Depresi Lansia Di Panti Sosial Lanjut Usia Harapan Kita Palembang Tahun 2022 - Eka Mutiara Sari, Oscar Ari Wiyansyah (Jurnal Kesehatan, 2023)
AbstractDepression is one of the mental disorders that are often found in the elderly due to the aging process. The purpose of this study was to determine the effect of Benson's relaxation technique on the level of depression in the elderly at the Harapan Kita Elderly Social Institution in Palembang. Therefore, non-pharmacological interventions are needed that do not cause side effects, one of which is the Benson’s relaxation technique. This study uses a quantitative method with a pre-experimental research design, namely a one group pre-test and post-test design approach, with a total sampling technique of 30 respondents. Data collection tool in the form of a Geriatric Depression Scale (GDS) questionnaire. The results of this study showed that the average value of elderly anxiety before Benson’s relaxation was 9.23, namely the level of moderate depression, with a standard deviation of 2.909. After using Benson's relaxation technique, the average value of depression in the elderly is 5.10, which is the level of mild depression, with a standard deviation of 2.670. With value 0.000, which means p <0.05. It was concluded that there was an influence between the Benson’srelaxation technique on the depression level of the elderly at the Harapan Kita Elderly Social Institution in Palembang in 2022, so it was suggested that Benson’s relaxation therapy could be used as one of the non-pharmacological interventions in the nursing home to reduce depression levels.Keywords : Benson’s Relaxation Technique, Depression Level, Elderly